Acid-assisted polysaccharides extracted from Asparagus cochinchinensis protect against Alzheimer’s disease by regulating the microbiota-gut-brain axis - Li, Ruixue; Wang, Hui; Wang, Qinjian; Zhang, Zhiqiang; Wang, Li (Frontiers in Nutrition, 2024)
In this study, an acid-assisted extraction strategy was used to extract a novel polysaccharide (ACP) from Asparagus cochinchinensis, after which this polysaccharide was purified and subjected to extensive characterization. ACP was determined to have an average molecular weight of 15,580 Da in structural characterization studies, and it was found to primarily consist of glucose, galactose, L-fucose, and fructose at an 82.14:12.23:2.61:2.49 ratio. Trace amounts of xylose, arabinose, and rhamnose were also detected in ACP preparations at a 0.48:0.04:0.02 ratio. GC-MS analyses identified eight different sugar linkages within ACP, including Glcp-(1→, →2)-Glcp-(1→, →6)-Glcp-(1→, →4)-Glcp-(1→, →3, 4)-Glcp-(1→, →2,4) -Galp-(1→, →4,6)-Galp-(1→, and →3,4,6)-Galp-(1→ linkages present at 23.